Effects of hydrogen peroxide on Scenedesmus obliquus: Cell growth, antioxidant enzyme activity and intracellular protein fingerprinting. (January 2022) - Zhang, Haihan; Zong, Rongrong; He, Huiyan; Huang, Tinglin
Abstract: Hydrogen peroxide (H2 O2 ) is an environmental-friendly algicide and it is widely used to control algal blooms in aquatic ecosystems. However, the response of algal cell metabolic characteristics and intracellular protein profile under H2 O2 stress is still not well understood. In the present study, the green alga Scenedesmus obliquus was exposed to different concentrations of H2 O2 (0, 2, 6, 8 and 10 mg L −1 ) to evaluate the changes in algal morphological, physiological, and proteomic features to H2 O2 exposure. The results showed that 8 mg L −1 of H2 O2 could effectively inhibit the cell growth and photosynthetic activity of S. obliquus including chlorophyll- a content and chlorophyll fluorescence parameters. The increased activities of superoxide dismutase (SOD) and catalase (CAT) observed in this study indicate that cells exposure to H2 O2 caused oxidative stress. The metabolic activity of S. obliquus was significantly decreased by H2 O2 treatment. In terms of proteomic analysis, 251 differentially expressed proteins (DEPs) were successfully identified. The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis revealed significant protein enrichment in the metabolic pathways, photosynthesis, ascorbic acid, and alginate metabolism and phenylpropane biosynthesis of S. obliquus . The analysis of protein-protein interaction system shows that the pathways of photosynthesis and metabolic pathways of S. obliquus were essential to resist oxidative stress. Taking together, these results shed new lights on exploring the cell physiological metabolism and intracellular protein mechanisms of H2 O2 inhibition on algal blooms. Graphical abstract: Image 1 Highlights: Cell chlorophyll fluorescence parameters were changed by H2 O2 stress. Superoxide dismutase and catalase activities were increased by H2 O2 stress. Carbon source metabolic activity was reduced by H2 O2 treatment. 251 significant proteins were identified by the iTRAQ technology. Photosynthesis and metabolic pathways were essential to resist H2 O2 stress.